POTENSI LARUTAN KAYU MANIS (Cinnamomum sp.) SEBAGAI LARVASIDA TERHADAP JENTIK Aedes aegypti - Riski Dwi Prameswari; Emilda agasvia; Siti Rofiqoh (Journals of Ners Community, 2022)
In Indonesia the use of cinnamon besides to cooking and as well as for health, such as for treatment and embalming mummies. The content of the main chemical compounds of cinnamon is cinnamic acid and cinnamaldehid. The cinnamaldehid is analogous cinnamic acid with a low molecular weight, these compounds have many activities, such as antipyretic, astringent, antibacterial, antifungal, antitumor. A wide variety of diseases that can be transmitted through mosquito bites, one of which is the dengue hemorrhagic fever, that is an acute febrile disease caused by the dengue virus, which enter the human bloodstream by mosquito bites of the genus Aedes sp., expecially Aedes aegypti or Aedes albopictus. This study aims to determine the potential of cinnamon solution as larvicides against Aedes aegypti. This type of study is experimental study that conducted in the laboratory by direct examination to see the effect of cinnamon solution against Aedes aegypti after direct contact for 24 hours. The results were analyzed using the analysis method of Anova one-way. The results of the statistically test obtained the significant values of larvae 24 hours was 0,000, thus H0 was rejected and H1 accepted, so that there was a significant difference in the potential of cinnamon solution mashed as larvicides against Aedes aegypti in concentration of 0.2%, 0.5%, 1% and 2%.